2017
DOI: 10.1371/journal.pone.0180836
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and biomimetic assessment of a hydraulic ankle/foot in level ground and camber walking

Abstract: Improved walking comfort has been linked with better bio-mimicking of the prosthetic ankle. This study investigated if a hydraulic ankle/foot can provide enough motion in both the sagittal and frontal planes during level and camber walking and if the hydraulic ankle/foot better mimics the biological ankle moment pattern compared with a fixed ankle/foot device. Five active male unilateral trans-femoral amputees performed level ground walking at normal and fast speeds and 2.5° camber walking in both directions u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…However, when walking or standing on uneven or sloped surfaces, the relative position of the body's COM to the lower limb joints changes and thus the alignment of a prosthesis may become sub-optimal. [15][16][17][18] Part of the problem may be the prosthetic device. In conventional, energy-storing-and-return (ESR) feet that have a fixed attachment to the distal end of the prosthetic pylon, plantarflexion and dorsiflexion of the foot are achieved through deformation of the foot keel, which is often constructed of elastic elements and structures.…”
Section: The Influence Of Prosthetic Ankles On the Standing Biomechanmentioning
confidence: 99%
“…However, when walking or standing on uneven or sloped surfaces, the relative position of the body's COM to the lower limb joints changes and thus the alignment of a prosthesis may become sub-optimal. [15][16][17][18] Part of the problem may be the prosthetic device. In conventional, energy-storing-and-return (ESR) feet that have a fixed attachment to the distal end of the prosthetic pylon, plantarflexion and dorsiflexion of the foot are achieved through deformation of the foot keel, which is often constructed of elastic elements and structures.…”
Section: The Influence Of Prosthetic Ankles On the Standing Biomechanmentioning
confidence: 99%
“…Most gait studies were carried out with TTAs and tests have been performed on level ground [ 8 , 9 , 11 ], slopes [ 12 , 14 ] and general outdoor walking conditions (including slopes and stairs) [ 7 ]. Two studies involved TFAs and both level ground and cross-slope walking were investigated [ 11 , 13 ]. It has been reported that the hydraulic ankle enables increased walking speed [ 9 , 11 ], a smoother transfer of plantar centre of pressure [ 8 , 11 ], a higher bio-mimicry of ankle resistance [ 13 ], and decreased peak internal stresses on the stump [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies involved TFAs and both level ground and cross-slope walking were investigated [ 11 , 13 ]. It has been reported that the hydraulic ankle enables increased walking speed [ 9 , 11 ], a smoother transfer of plantar centre of pressure [ 8 , 11 ], a higher bio-mimicry of ankle resistance [ 13 ], and decreased peak internal stresses on the stump [ 7 ]. However, other research reported no significant differences in the torque at the distal end of the socket in TTAs during slope ambulation when using hydraulic ankle-foot devices compared with other ankle-foot designs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations